Stronger VET für better lives : Cedefop's monitoring report on vocational education and training policies 2010-14 - (:unkn) unknown (Publications Office of the European Union, 2015)
This report provides a comprehensive overview of what European countries (EU Member States, Norway, Iceland and candidate countries) have done in the period 2011-2014 to address the priorities set for VET in 2010 in the Bruges communiqué as well as the 2020 objectives set for education and training of Europe's overall 2020 strategy. The key conclusion of the report is that European countries' joint work on vocational education and training (VET) shows clear signs of progress but there is more to do. "In many countries, the Bruges communiqué of 2010 has inspired systemic reforms focusing on learning-outcomes-oriented standards and curricula. In several cases, these were triggered by the work on qualifications frameworks. In other countries, the main impact of the communiqué is reflected in their work on apprenticeships but there are challenges in securing its quality. The development of national qualifications frameworks (NQFs), measures to reduce early leaving, and policies to promote lifelong learning for low-skilled and other groups at risk have also been high on national policy agendas. Work on the European tools will need to ensure they interact better with and focus more on European citizens and employers to produce the intended benefit. Other challenges include better use of information on labour market outcomes of VET graduates, strengthening efforts to promote creativity, innovation and entrepreneurship in VET, and ensuring professional development opportunities for VET teachers and trainers." (Publisher, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2 Europa; EU-Bildungspolitik; Berufsbildung; Indikatoren; Monitoring; Europa